IFR: SEBELUM DAN SESUDAH TANGGAL PENGUMUMAN TERHADAP HARGA SAHAM DAN VOLUME PERDAGANGAN SAHAM TINJAUAN PERSPEKTIF TRADING VOLUME ACTIVITY - Deni Juliasari; Zainal Arifin (UPT Penerbitan Universitas Jember)
This study aimed to determine the effect of Internet Financial Reporting (IFR) on stock price movements and trading volumes. This research is a quantitative approach. The data used in this study is the data crossection. The number of samples in this study is a total of 49 companies listed on the Stock Exchange which reported an annual report for the period 2015 either over the internet or website. Results showed results that can give the conclusion that the IFR does not make a difference to the stock price and the volume of trade in shares with a range of observations 5 days before and 5 days after the date of announcement of this suggests the announcement of financial statements do not contain information of interest to investors to react to the announcement financial statements.